8-Nitrotryptanthrin inhibits colorectal cancer progression via TGF-β/SMAD and PI3K/AKT/mTOR pathways - Sun, Cheng-Yu; Cong, Kai-Ping; Zhao, Dan-Dan; Fan, En-Guo; Guo, Ming-Quan; Zhang, Zheng-Guo (Frontiers in Pharmacology, 2025)
ObjectiveTo investigate the anticancer effects and underlying mechanisms of 8-nitrotryptanthrin (8-Nitrotryp) against colorectal cancer (CRC).MethodsThe effects of 8-Nitrotryp on proliferation, colony formation, and migration were evaluated in HCT116 and SW480 cells, with comparisons to its parent compound tryptanthrin (Tryp). Mitochondrial membrane potential (MMP) was assessed using JC-1 staining, and early apoptosis was analyzed by flow cytometry. Proteomic analysis and Western blotting were employed to examine the modulation of the phosphatidylinositol 3-kinase (PI3K)/protein kinase B (AKT)/mechanistic target of the rapamycin (mTOR) pathway and transforming growth factor-β (TGF-β)/Sma- and Mad-related proteins (SMAD) signaling pathways, as well as epithelial–mesenchymal transition (EMT).Results8-Nitrotryp significantly inhibited proliferation of HCT116 (IC50 = 0.81–1.08 μM; P < 0.001) and SW480 cells (IC50 = 0.76–1.59 μM; P < 0.001), suppressed colony formation of HCT116 (P < 0.001 at 1 μM) and SW480 cells (P < 0.001 at 2 μM), and inhibited migration in a dose-dependent manner (0.5–2 μM), demonstrating greater potency than Tryp. It also suppressed MMP and induced early apoptosis in HCT116 (P < 0.001 at 1 μM) and SW480 cells (P < 0.001 at 0.5 μM). Proteomic analysis and Western blotting revealed that 8-Nitrotryp downregulated PI3K expression, inhibited the phosphorylation of AKT and mTOR, and reduced TGF-β1-induced SMAD2 phosphorylation. Additionally, 8-Nitrotryp suppressed the EMT process.Conclusion8-Nitrotryp inhibits CRC progression by modulating the TGF-β/SMAD and PI3K/AKT/mTOR pathways, highlighting its potential as a multi-target therapeutic agent for CRC and warranting its further investigation.Novelty and ImpactCRC is a global health challenge with limited treatments for advanced stages. This study provides the first evidence of 8-Nitrotryp’s antitumor efficacy in CRC, demonstrating its dual inhibitory activity on the TGF-β/SMAD and PI3K/AKT/mTOR pathways. Compared to Tryp, 8-Nitrotryp exhibits markedly enhanced potency, with lower IC50 values due to the introduction of a nitro group. Furthermore, the suppression of EMT is mechanistically linked to TGF-β/SMAD pathway inhibition. These findings suggest 8-Nitrotryp’s potential as a novel therapeutic for CRC.